Artificial muscles powered by glucose - Mashayekhi Mazar, Fariba; Martinez, Jose G.; Tyagi, Manav; Alijanianzadeh, Mahdi; Turner, Anthony P. F.; Jager, Edwin W. H. (Wiley, 2019)
Untethered actuation is important for robotic devices to achieve autonomous motion, which is typically enabled by using batteries. Using enzymes to provide the required electrical charge is particularly interesting as it will enable direct harvesting of fuel components from a surrounding fluid. Here, a soft artificial muscle is presented, which uses the biofuel glucose in the presence of oxygen. Glucose oxidase and laccase enzymes integrated in the actuator catalytically convert glucose and oxygen into electrical power that in turn is converted into movement by the electroactive polymer polypyrrole causing the actuator to bend. The integrated bioelectrode pair shows a maximum open‐circuit voltage of 0.70 ± 0.04 V at room temperature and a maximum power density of 0.27 µW cm−2 at 0.50 V, sufficient to drive an external polypyrrole‐based trilayer artificial muscle. Next, the enzymes are fully integrated into the artificial muscle, resulting in an autonomously powered actuator that can bend reversibly in both directions driven by glucose and O2 only. This autonomously powered artificial muscle can be of great interest for soft (micro‐)robotics and implantable or ingestible medical devices manoeuvring throughout the body, for devices in regenerative medicine, wearables, and environmental monitoring devices operating autonomously in aqueous environments
Keywords: polypyrrole; laccase; glucose oxidase; electroactive polymers; artificial muscles